Elasticity and Lipids Changes in Children with Type I Diabetes Mellitus Compared with Controls and the Effect of Lipids on Elasticity in Diabetic Children - Noori Noor Mohammad; Teimouri Alireza; Moghadam Maryam Nakhaei (Sciendo, 2023)
Increased atrial elasticity is a marker of cardiovascular events. This study aimed to compare the parameters of elasticity and lipids in children with type 1 diabetes mellitus (TIDM) compared with controls and the effect of lipids on elasticity in children with diabetes.